2008
DOI: 10.1002/cphc.200800016
|View full text |Cite
|
Sign up to set email alerts
|

The Electrochemical Grafting of a Mixture of Substituted Phenyl Groups at a Glassy Carbon Electrode Surface

Abstract: Two-component substituted aryl groups are simultaneously grafted onto the surface of a glassy carbon electrode by electrochemical reduction of a binary mixture of two aryl diazonium salts in acetonitrile. The electrochemical deposition is achieved potentiostatically and two different mixtures with four different ratios of diazonium salts are used. The binary mixtures comprise: 1) 4-nitrophenyl diazonium and 4-bromophenyl diazonium cations and 2) 4-bromophenyl diazonium and N,N-diethylaniline diazonium cations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 65 publications
8
40
0
Order By: Relevance
“…For Br À Ar À and O 2 N À Ar À mixed layers modified GC surface, N1s core level spectra displays the characteristic peaks at 406 eV and 400 eV, which can be attributed to the nitrogen atom of the nitro groups and to the reduction of nitro groups to amino groups during the XPS analysis chamber during the measurements [45] or during the electrochemical grafting step in aqueous medium [16], respectively. This is in good agreement with the literature [35]. The absence of a N1s peak at 403.8 eV confirms that unreacted diazonium species are not present at the surface [43].…”
Section: Xps Characterization Of Mixed Layers Modified Gc Surfacessupporting
confidence: 91%
See 2 more Smart Citations
“…For Br À Ar À and O 2 N À Ar À mixed layers modified GC surface, N1s core level spectra displays the characteristic peaks at 406 eV and 400 eV, which can be attributed to the nitrogen atom of the nitro groups and to the reduction of nitro groups to amino groups during the XPS analysis chamber during the measurements [45] or during the electrochemical grafting step in aqueous medium [16], respectively. This is in good agreement with the literature [35]. The absence of a N1s peak at 403.8 eV confirms that unreacted diazonium species are not present at the surface [43].…”
Section: Xps Characterization Of Mixed Layers Modified Gc Surfacessupporting
confidence: 91%
“…For example, the atomic ratio for Br and S on GC electrode surface is 1 : 5.75, indicating that the modification layer is dominated by HS À Ar À . Thus, the aryl diazonium cations with the more anodic reductive adsorption potential (HS À Ar À N 2 þ ) dominate on the surface with the in situ generated aryl diazonium salt, which is consistent with the results reported by Belanger and co-workers for presynthesized aryl diazonium salts [35]. The same trend is observed for the other seven mixed…”
Section: Comparison Of Mixed Layers On Gc and Gold Surfaces And Compasupporting
confidence: 90%
See 1 more Smart Citation
“…This is presumably due to differences in the rates of attachment of the two amines to the GC surface: attachment of HDA-Boc is presumably favoured over 1-BA, hence the unexpectedly high amount of osmium complex even at low percentages of HDA-Boc in solution. 27 The surface coverages measured for complex 5 fall within the range expected given the size of the complex determined by theoretical calculation with a coverage of 16 -18 pmol cm -2 consistent with model b above in which once coupled to the surface the complex hinders subsequent coupling to amines within its radius of gyration. This also explains why a significant amount of immobilised complex 5 is found even at the lowest (0.1%) linker ratio in solution.…”
Section: Synthesis and Characterization Of Bis-(22'-bipyridyl)(4-(pysupporting
confidence: 78%
“…[56] Recently, Downard et al published the micro-and nanoscale patterning of carbon surfaces with different organic functionalities using soft lithography, AFM, and electrochemically assisted grafting. [57,58] Gooding et al, [59] and more recently BØlanger et al, [60] have reported another interesting method for the simultaneous bifunctionalisation of a GC electrode by differently substituted phenyl groups, achieved by electrochemical reduction from a solution containing a mixture of the corresponding diazonium salts. The major disadvantage of using electrochemical reduction of substituted aryl diazonium salts for surface modification is the low stability and availability of diazonium salts bearing suitable functional groups.…”
Section: Introductionmentioning
confidence: 98%